Introducción y evaluación de ecotipos de piñón (Jatropha curcas L.) - Echeverría Trujillo, Ronal Gabriel; Valles Ramírez, Ayda Karin; Rengifo Gonzales, Livinston; Pinedo Grandes, Magno (INIA. Estación Experimental Agraria El Porvenir - San Martín, 2019)
6 páginas.